Composition and health of fish in refugia habitat of ephemeral tributaries to the lower Zambezi in southern Africa - Strauch AM; Kapust AR; Jost, Christine (Commonwealth Scientific and Industrial Research Organisation, 2015)
The ecology of dryland rivers is under-studied in Africa. During seasonal droughts, these rivers cease flowing resulting in disconnected pools that restrict the movement of aquatic species. Few studies have focussed on the conditions of these refugia or their effect on fish. We investigated the influence of pool size and water quality on the abundance and composition of fish, including body condition (BC) and a quantitative heath assessment index (HAI) of individual species in tributaries of the lower Zambezi during the dry season. Although no single species was found among all sites, species in either or both the Cichlidae or Cyprinidae families were recovered in 12 of 15 locations. Fish biomass and richness were positively correlated with refugia size. As water quality declined, Cichlidae BC declined while Cyprinidae BC improved. By contrast, both Cichlidae HAI and Cyprinidae HAI were positively related (declined) to increased dissolved oxygen while negatively related to nutrients. We conclude that refugia conditions affect fish communities but the direction of effect can be species dependent. Increasing our understanding of the effects of land-use and water-use on habitat quality and their consequences for freshwater ecosystems in general should be an important goal towards improving rural livelihoods.